Understanding the pomology of the planar cordon tree architecture in apple : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Horticulture at Massey University, Palmerston North, New Zealand - Wilson, Jack (Massey University, 2020)
Future Orchard Planting Systems (FOPS) is a radical new concept for orchard systems aimed at doubling the productivity of New Zealand orchards across key fruit sectors. The programme incorporates new orchard configurations using a two-dimensional planar tree architecture designed to harness ≥ 85% seasonal radiation when fully-grown. Metrics to manage fruit density, fruit quality and return bloom have not yet been calibrated for new planar tree designs. Additionally, the understanding around the light environment of this new two-dimensional system is unknown. Therefore, four and five-year-old planar cordon trees of ‘Royal Gala’ and ‘Scifresh’ (Jazz™) were used in 2018 and 2019 to investigate relationships between the final crop density (fruit no/cm² BCA) and the light environment on yield and fruit quality at harvest. Individual fruit weights from each branch unit were quantified at harvest using an electronic weight sizer and Invision system (Compac New Zealand). Branch unit fruit density present after hand thinning ranged from 1.8 to 13.5 fruit/cm² BCA in 2018 and 2.5 to 28 fruit/cm² BCA in 2019. Crop densities in the upper range were nearly five times that typically used for branch units in conventional tall spindle trees. As crop density increased, fruit weight did not change. A simple linear correlation suggests that for both cultivars the relationship between fruit weight and crop density was weak, with r² values ranging from 0.004 to 0.108 in 2018 and 0.024 to 0.248 in 2019. Fruit density did not affect fruit size below 28 fruit/cm² BCA. However, there was evidence of reduced return bloom at the closer, 1.5 m row spacing for ‘Scifresh’ only in 2018. Light measurements at 5 different heights in the planar canopies were completed over four complete replicate days during January 2019. Light readings were recorded using a LI-COR data logger and ‘Palmer’ sensors fixed onto a vertical steel rod placed within the tree. Light irradiance ranged from approximately 60 to 1419 µmol/m²/s in the middle of the day. A simple regression suggested that light energy received at each position was higher in the top of the canopy compared to the bottom, with r2 values of 0.979 for ‘Royal Gala’ and 0.965 for ‘Scifresh’. A typical level of light in this planar canopy would reach 12% at the bottom, 32% in the middle and 60% at the top in terms of percentage of total incoming radiation. Leaf area index at a whole tree level (uprights as well as the cordon) within the planar cordon system (Vertical canopy only) ranged from 3.1 – 4.0 at the 1.5 m spacing and 2.6 – 3.1 at the 2.0 m row spacing, consequently producing high yields at 132-159 t/ha at 1.5 m (planting density of 2222 trees/ha) and 115-121 t/ha at 2.0 m row spacing (planting density of 1667 trees/ha) for ‘Royal Gala’ and ‘Scifresh’. Fresh fruit weight, dry matter content, red colour and specific leaf weight increased with increasing height in the canopy. These fruit quality attributes also showed positive correlations with the daily light integral (mol/m²). We discuss the implications of these findings for yield and fruit quality optimisation within this planar cordon planting system. It was concluded that crop loading metrics for this planar cordon training system differ in comparison to the conventional tall spindle design. The light environment increased with canopy height and successfully supported the production of high quality fruit in terms of fruit size, colour and dry matter content. Future work directions may include quantifying the performance of this system at full canopy development as well as assessing the internal quality of fruit grown on a 2D planar cordon training system.
Keywords: 300802 Horticultural crop growth and development